2020
DOI: 10.2478/agri-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Titanium Oxide Nanoparticles Can Stimulate Plant Growth and the Photosynthetic Pigments on Lettuce Crop

Abstract: Our knowledge of the bioactivity of silicon titanium oxide nanoparticles (TiSiO4 NPs) in crops is scarce, contrarily to TiO2NPs and SiO2NPs that are used in many industrial sectors, and have emerged in nanoagriculture (e.g., as pesticides or nanofertilisers). To evaluate the potential of using TiSiO4 NPs in nanoagriculture, it is necessary to characterize their potential benefits on crops and the safety doses. Here, we report for the first time the bioactivity of TiSiO4 NPs (up to 100 mg/L) in the model crop l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…However, induction of oxidative stress due to the formation of free radicals is the key process by which various natural and synthetic materials induce deleterious effects in tissues. Among different NPs, SiO 2 NPs are widely used in biomedical applications including labeling, biosensors, medical diagnosis, in vivo imaging, degradation of toxicants, and delivery of drugs and antibodies. Apart from the reported toxicity of C-SiO 2 , its coating and mixing are frequently done to enhance the stabilization of NPs. This is usually done for chemical inertness enhancement, avoidance of agglomeration, temperature resistance, high biocompatibility, and resistance to decomposition .…”
Section: Introductionmentioning
confidence: 99%
“…However, induction of oxidative stress due to the formation of free radicals is the key process by which various natural and synthetic materials induce deleterious effects in tissues. Among different NPs, SiO 2 NPs are widely used in biomedical applications including labeling, biosensors, medical diagnosis, in vivo imaging, degradation of toxicants, and delivery of drugs and antibodies. Apart from the reported toxicity of C-SiO 2 , its coating and mixing are frequently done to enhance the stabilization of NPs. This is usually done for chemical inertness enhancement, avoidance of agglomeration, temperature resistance, high biocompatibility, and resistance to decomposition .…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed that, nanoparticles enter plant's metabolic pathway and help with disease resistance, better growth, and high yield [23,24]. Silicon (Si) has numerous constructive impacts on plants growth, growing under various types of stresses [25]. Si signi cantly improves resistance ability of plants against several stresses like drought[26], nutrient imbalances, higher radiation, metal toxicity and higher salinity [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoagriculture is opening a new era in the agro-food industry by playing an emergent role in improving crop production, providing highly efficient and sustainable nanopesticides, nanofertilizers, and nanosensors [1][2][3][4][5][6]. Several metal-based nanoparticles (NPs), particularly silver (Ag), copper (Cu), iron (Fe), titanium (Ti), and zinc (Zn) NPs, are increasingly being used to promote crop germination and plant growth, to improve stress Agriculture 2022, 12,190 2 of 14 tolerance, or in the amendment of agricultural soils [1,7,8].…”
Section: Introductionmentioning
confidence: 99%